Self‐efficacy in the context of nursing education and transition to practice as a registered practitioner: A systematic review - Mousa Abusubhiah; Nuala Walshe; Rena Creedon; Brendan Noonan; Josephine Hegarty (Wiley, 2023)
Abstract Aim The aim of this systematic review is to identify, describe and synthesize evidence from experimental studies conducted to measure and conceptualize self‐efficacy within the context of nursing education and the transition of nursing students to practice as a registered practitioners. Design Systematic review. Methods Papers were screened by four independent reviewers, and data were extracted using a standardized data extraction tool. The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidance and checklists were used to guide this review. Results The review included 47 studies, using a quasi‐experimental pre‐test-post‐test design (n = 39) and randomized control trials (n = 8). Various teaching and learning interventions were used to enhance self‐efficacy; however, there is no definitive conclusion to be drawn regarding the most effective educational interventions. Various instruments were used in the studies to measure self‐efficacy. 10 of these were related to general self‐efficacy, while 37 instruments measured self‐efficacy in the context of specific skills.